Up-Converting Lanthanide-Doped YAG Nanospheres - Vallés-Pelarda, Marta; Sanchez, Rafael S.; Barea, Eva M.; Mora-Seró, Iván; Julián-López, Beatriz (Frontiers in Materials, 2020)
The development of lanthanide-doped Y3Al5O12 (Ln:YAG) garnet nanostructures is a hot topic in the field of inorganic nanophosphors due to the current interest in developing small nanoparticles for solid-state lighting (SSL), displays, lasers and scintillation applications. In this study, we report the preparation of homogeneous Ln:YAG (Ln: Ho/Yb ions) nanospheres through a combined two-steps coprecipitation-solvothermal synthesis at low temperature. The crystal growth takes place in ethylene glycol, which is an inexpensive, non-toxic and easily available solvent. Monodisperse and crystalline spherical YAG particles of 80 nm in diameter were obtained. Furthermore, the protocol can be extended to other compositions (Tb/Yb, Tm/Yb…) to explore different luminescent properties, without affecting the morphology of the material, indicating the robustness and practical utility of the reported methodology. Thermal treatment of the nanogarnets at 1200ºC is necessary for making materials optically active upon both UV and NIR excitation. The spherical morphology of annealed samples is preserved, what helps their further dispersion in solvents, barbotines, inks or printing vehicles. The lanthanide-doped nanogarnets exhibited the characteristic blue, green and red emissions from lanthanide upconversion photoluminescence (UCPL) upon NIR excitation. The UCPL mechanism was studied and CIE chromate coordinates were obtained. These nanogarnets were further evaluated as functional ceramic phosphors by incorporating them into commercial glazes. The materials exhibited an exceptional chemical stability in a harsh medium such as a fused glaze. Consequently, the visible emissions of the nanoparticles were transferred to the whole glass matrix, thus providing a functional glaze that emits intense blue and green light upon NIR excitation. These luminescent nanogarnets have promising applications in smart enamels, but can also be useful for lighting displays (white LEDs…), smart paintings or plastics, and anti-counterfeiting systems.